Surveillance on Tactile-Based Media Accessibility Levels for the Visually Impaired in Bandung Train Stations - Fadhlillah, Fariz (INKLUSI, 2022)
This paper intended to survey tactile-based media accessibility levels for the visually impaired in train stations incorporated in Operational Region II Bandung. Data collection got conducted on interviews with 30 visually impaired. Research objects included context as an orientation and mobility (OM) system as stated in 'Regulation of the Minister of Transportation of the Republic of Indonesia Number 36 of 2019 concerning Minimum Service Standards for Transporting People by Train' and 'Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 14 of 2017 concerning the Requirements for Building Facilities Convenience’, namely: tactile paving, braille sign , signage, map, information board, and ticket. Generally, the visually impaired did not receive good minimum services at the station since the universal design principles had not yet get applied to design tactile-based accessibility standards. The accessibility levels of those media came from the visually impaired pragmatical usage.